Pengaruh perlakuan pendahuluan pulse electric field (PEF) pada konvektif kinetika pengeringan dan mikrostruktur daun kelor (Moringa oleifera) - Muhammad Yusuf Rachmadianto; Sukardi Sukardi; Dodyk Pranowo (AGROINTEK, 2024)
Moringa leaves (Moringa oleifera) are a "Superfood" food ingredient rich in protein, phenolics, amino acids, and unsaturated fatty acids that benefit human health. Consumption in fresh form is prevalent, but the last decade has been plentiful in dry preparations. Pulse Electric Field (PEF) is one of the important preliminary treatments in drying vegetables and fruits. Electroporation on Moringa leaves is applied to determine the effectiveness and efficiency of drying on the leaves. The study aimed to determine the effect of PEF treatment before drying on the kinetics of drying and the microstructure of Moringa leaves. PEF treatment is carried out at voltages of 1000V, 1500V, 2000V and without PEF as a control. The treatment during drying was observed at the level of moisture content and effective diffusivity on each of the PEF and control treatments. Experimental data were entered into seven mathematical models and evaluated through Lewis, Page, Modified Page, Logarithmic, Two-term, Wang and Singh, and Simple exponential models. The results of the evaluation of the drying model were selected as the best drying mathematical model on the Logarithmic model. The highest diffusivity effective value at PEF with a voltage of 2000V of 3.25 × 10−9 m2/s. In the microstructure changes of Moringa leaves, the preliminary PEF treatment was conducted using the scanning electron microscope (SEM) test. Moringa leaves with pretreatment PEF 2000V color analysis was lightness (L*), redness (a*), yellowness (b*), and ∆E values of 41.74±0.34a, -8.64±0.28c, 20.16±0.94a, 7.08±0.53c. The results of moringa leaves extract with pretreatment PEF 2000V were total phenols and IC50 values of 55.60±1.24d mg GAE/gram and 76.79±0.77a ppm. Implementing PEF preliminary treatment on drying is expected to accelerate the drying process and maintain a decrease in the quality of the final product of Moringa leaves.